Effect of SCARA Robot speed on bottle cap fitting on rotary indexing table - Simanullang, Aldi; Risfendra (Department of Electrical Engineering Universitas Negeri Padang, 2025)
In the Industry 4.0 era, the integration of SCARA robots with rotary indexing tables has significantly improved automation in assembly processes, particularly in bottling lines. This study investigates the effect of speed variation of the SCARA robot on the accuracy and quality of bottle cap installation using a rotary indexing table. The system was developed using a Siemens S7-1200 PLC, an Epson T6 SCARA robot, and supporting actuators such as pneumatic cylinders and stepper motors. Experiments were conducted at five different robot speeds: 10%, 20%, 30%, 40%, and 50%, with five trials for each setting. The results show a 100% success rate at 10%, 20%, and 30% speed, with proper alignment between the bottle and cap. However, at 40% speed, the success rate dropped to 85% due to minor misalignment. At 50% speed, the assembly failed completely due to synchronization issues and excessive force, resulting in a 0% success rate. These findings emphasize the importance of speed optimization to maintain synchronization between the SCARA robot and the rotary indexing table, ensuring an efficient and accurate automated bottling process